Effect of gender on students' performance and motivation in electricity teaching using interactive simulations - Ben Ouahi Mhamed; Droui Mohamed; Zghida Nour-eddine; Hida Elyazid (SHS Web of Conferences)
This study examines the effect of gender on the performance and motivation of middle school students in electricity, using interactive simulations (IS). A total of 127 students were divided into two groups: a control group (n = 65) receiving traditional instruction, and an experimental group (n =6 2) using IS. Performance and motivation were measured by tests (pretest and posttest) and a questionnaire. Results showed a significant difference in favor of girls in the pre-test, but no significant difference between genders in the post-test for the experimental group. In addition, using IS improved student motivation compared with the traditional method. These results suggest that interactive simulations are an effective strategy for encouraging students' active participation in physical science, particularly electricity, and can help reduce gender performance gaps while improving overall student performance.